Education of Cardiovascular Disease in the Elderly through Health Seminars and Health Corner - Silitonga, Hanna Tabita Hasianna; Panggabean, Ronald Torang Marsahala; Rambung, Etha; Adrianto, Hebert; Sheyoputri, Rytney Electra; Xena, Leora Esther (P3KM Politeknik Pertanian Negeri Samarinda, 2024)
Advanced age or elderly refers to individuals who have reached the age of 60 and above. According to data from the National Socioeconomic Survey in March 2020, there is a total of 10.48%, consisting of 51.81% elderly women and 48.19% elderly men. The elderly population undergoes the aging process, making them at a higher risk of degenerative diseases. According to Basic Health Research in 2013, the most common diseases among the elderly are hypertension (57.6%), arthritis (51.9%), stroke (46.1%), dental and oral problems (19.1%), chronic obstructive pulmonary disease (8.6%), and diabetes mellitus (4.8%). Hypertension can lead to other disorders, such as cardiovascular disease. Cardiovascular diseases have a high mortality rate and can be caused by various factors, such as diabetes mellitus and obesity resulting from an unhealthy lifestyle. Therefore, through education on cardiovascular diseases and the formation of elderly cadres and health corners, efforts to prevent cardiovascular diseases in the elderly are expected to be optimally implemented. The main target of this program is the congregation of the Indonesian Christian Church (GKI) in Sepanjang Sidoarjo, Taman District, Sidoarjo Regency. Activities include pre-tests and post-tests related to cardiovascular diseases in the elderly, health seminars, and the establishment of health corners. The results of this activity show that the respondents' knowledge level, assessed through questionnaires, had an average pre-test score of 12.52 and a post-test score of 14.71, indicating a significant change with a p-value < 0.001 meeting the significant level of 95%.